Lauren Lefitz: capstone - Lefitz, Lauren, artist (Colorado State University. Libraries, 2022)
The artist's statement: My best forms of communication have been through painting and graphic design. I can convey my feelings and poignant concepts via 2D images. I discuss natural resource management, sustainability, and my own outdoor experiences in my work. My digital work uses straightforward designs, minimal typography, and restrained color palettes to enable a more direct form of communication. Similar to how I create graphics on my computer, I communicate more of my feelings through movement when I paint. This is a more intimate kind of art creation than when I create graphics on my computer. Through the simplicity of my design work, I am able to clearly communicate messages about preventing environmental catastrophes through policy, facts, preservation, and discussion. I use aesthetics found in nature, and earth tones are always a part of my color palette. I take shapes and patterns found in the natural world to make people think about their personal impact and what more they can do. I always make sure to practice what I preach when it comes to my personal impact. My design work is created through experience and the connections I make with people and the environment.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design